(Arylsulfinyl)difluoromethylation of Alkyl Halides: Facile Access to Diverse Fluorinated Compounds. Issue 48 (28th December 2020) - Liu, Hefu; Wang, Zhongyi; Li, Xiangye; Diao, Zhengzhen; Liu, Hui; Sun, Fenggang; Li, Yueyun; Dong, Yunhui; Li, Xinjin
Abstract: A facile and efficient (arylsulfinyl)difluoromethylation of alkyl halides with aryl difluoromethyl sulfoxide (ArSOCF2 H) has been developed. The reaction tolerates a variety of functional groups and afford the (arylsulfinyl)difluoromethylated products in moderate to good yields. Reduction of the sulfoxide products can conveniently afford aromatic difluoroalkylsulfides in good yields and the transformation of phenylsulfinyl group to other useful moieties is also accomplished. It is noted that the difluoromethyl heteroaryl sulfoxides (2‐PySOCF2 H and BTSOCF2 H) give heteroaryl thioethers rather than difluoroalkyled sulfoxides by removal of carbonylfluoride (COF2 ). Abstract : An efficient method for nucleophilic (arylsulfinyl)difluoromethylation of alkyl halides with aryl difluoromethyl sulfoxides has been developed. The reaction tolerates various functional groups and afford the difluoroalkyled sulfoxides in moderate to good yields. The products could be conducted further transformations to diverse fluorinated compounds, such as difluoroalkylsulfides, difluoromethyled product and difluoroalkylsilane.